Parametri pedologici e applicazioni per modelli in ambito ambientale: il quadro europeo ed italiano - Lupia, Flavio; Vanino, Silvia; Laruccia, Nicola (GEOmedia, 2010)
Soil parameters as a key point for environmental modeling: the European and Italian situation Soil parameters are key information for environmental modelling and simulation activities. Soil data demand grows contemporary to the need of supporting the decision processes at the different administrative levels. Models application requires collection, harmonization and integration of soil database at the various geographic levels as well as the assessment of the characteristics of data accuracy and quality. The contribution explores the European and Italian situation concerning soil databases by stressing their features, issues and future perspectives.